A prospective comparison of Scheimpflug-based anterior segment imaging systems in normal and abnormal corneas: Oculus Pentacam vs. Remidio Visionix VX650 - Kumar, Sonam; Negiloni, Kalpa; Gupta, Parul Chawla; K, Ranjitha; N, Neha; Parthasarathy Rao, Divya; Damani, Jyothi; Thakur, Ritika; Ballae Ganesh Rao, Shonraj; Duggal, Mona (Frontiers in Ophthalmology, 2025)
PurposeAdvancements in anterior segment imaging have significantly improved the precision of corneal diagnostics, aiding ocular conditions management. The study evaluated the agreement between two Scheimpflug devices—Pentacam and Remidio Visionix 650 (VX650)—in assessing corneal and anterior chamber parameters in patients with and without corneal abnormalities.Materials and methodsThis prospective study at a tertiary eye care hospital measured pachymetry values (central corneal thickness, thinnest point), front corneal surface parameters (keratometry, curvature, astigmatism), back corneal surface parameters (elevation, curvature) and anterior chamber parameters (depth, volume, angle). Bland-Altman analysis assessed agreement between the devices, and the Intraclass Correlation Coefficient (ICC) evaluated VX650’s repeatability.ResultsOf the 202 patients (mean age was 25 ± 4.33 years), 141 eyes were classified as normal and 61 as abnormal (41 keratoconus, 17 post-LASIK, 3 post-ICL). Bland-Altman analysis showed good agreement between Pentacam and VX650 for anterior segment parameters. The VX650 measured marginally thicker corneal thickness (mean difference of central corneal thickness (CCT) of -4.0 ± 6.3 µm). Statistically significant differences in apical corneal thickness were noted for post-refractive surgery patients. K1 and K2 values showed significant variations in keratoconus but were not clinically significant. Anterior chamber depth was similar between devices, though volume differences were observed post-surgery. ICC indicated good to excellent repeatability (above 0.75) for most parameters.ConclusionRemidio Visionix VX650 showed good agreement with Pentacam for key anterior segment measurements, confirming its reliability for corneal diagnostics. Additionally, its multifunctional capabilities offer potential for streamlining workflows, especially in clinics seeking efficient, comprehensive eye assessments.